Cord blood cardiovascular biomarkers in tetralogy of fallot and D-transposition of great arteries - Gómez, Olga; Nogué, Laura; Soveral, Iris; Guirado, Laura; Izquierdo, Nora; Pérez-Cruz, Miriam; Masoller, Narcís; Escobar, María Clara; Sanchez-de-Toledo, Joan; Martínez-Crespo, Josep Maria; Bennasar, Mar; Crispi, Fàtima (Frontiers in Pediatrics, 2023)
Previous reports suggest that cord blood biomarkers could serve as a prognostic tool for conotruncal congenital heart defects (CHD). We aimed to describe the cord blood profile of different cardiovascular biomarkers in a prospective series of fetuses with tetralogy of Fallot (ToF) and D-transposition of great arteries (D-TGA) and to explore their correlation with fetal echocardiography and perinatal outcome. Methods: A prospective cohort study (2014-2019), including fetuses with isolated ToF and D-TGA and healthy controls, was conducted at two tertiary referral centers for CHD in Barcelona. Obstetric ultrasound and fetal echocardiography were performed in the third trimester and cord blood was obtained at delivery. Cord blood concentrations of N-terminal precursor of B-type natriuretic peptide, Troponin I, transforming growth factorβ (TGFβ), placental growth factor, and soluble fms-like tyrosine kinase-1 were determined. Results: Thirty-four fetuses with conotruncal-CHD (22 ToF and 12 D-TGA) and 36 controls were included. ToF-fetuses showed markedly increased cord blood TGFβ (24.9 ng/mL (15.6-45.3) vs. normal heart 15.7 ng/mL (7.2-24.3) vs. D-TGA 12.6 ng/ml (8.7-37.9); p = 0.012). These results remained statistically significant even after adjusting for maternal body mass index, birth weight and mode of delivery. TGFß levels showed a negative correlation with the pulmonary valve diameter z-score at fetal echocardiography (r=-0.576, P=0.039). No other differences were found in the rest of cord blood biomarkers among the study populations. Likewise, no other significant correlations were identified between cardiovascular biomarkers, fetal echocardiography and perinatal outcome. Conclusions: This study newly describes increased cord blood TGFβ concentrations in ToF compared to D-TGA and normal fetuses. We also demonstrate that TGFβ levels correlate with the severity of right ventricle outflow obstruction. These novel findings open a window of research opportunities on new prognostic and potential preventive strategies.